2012
DOI: 10.1164/rccm.201202-0309oc
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role for p130Cas in the Progression of Pulmonary Hypertension in Humans and Rodents

Abstract: Our findings demonstrate that p130(Cas) signaling plays a critical role in experimental and idiopathic PAH by modulating pulmonary vascular cell migration and proliferation and by acting as an amplifier of RTK downstream signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0
4

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 48 publications
3
93
0
4
Order By: Relevance
“…Indeed, accumulating evidence supports the concept that increased endothelial apoptosis at the early stage and decreased endothelial apoptosis at later stages of the disease could contribute to PAH [18]. Consistent with this hypothesis, we have recently reported that primary pulmonary endothelial cells generated from PAH lung specimens exhibit various intrinsic abnormalities and present a modified pro-proliferative, apoptotic-resistant phenotype [4,17,19]. Although we have shown that increased activity of the FGF2 autocrine loop is among the mechanisms needed to acquire this altered endothelial phenotype in PAH [17], the exact nature of pulmonary endothelial cell modification during PAH and the balance between apoptotic and anti-apoptotic phenotypes remain only partially understood.…”
Section: Circulating Microparticles As Regulators Of Endothelial Dysfsupporting
confidence: 69%
“…Indeed, accumulating evidence supports the concept that increased endothelial apoptosis at the early stage and decreased endothelial apoptosis at later stages of the disease could contribute to PAH [18]. Consistent with this hypothesis, we have recently reported that primary pulmonary endothelial cells generated from PAH lung specimens exhibit various intrinsic abnormalities and present a modified pro-proliferative, apoptotic-resistant phenotype [4,17,19]. Although we have shown that increased activity of the FGF2 autocrine loop is among the mechanisms needed to acquire this altered endothelial phenotype in PAH [17], the exact nature of pulmonary endothelial cell modification during PAH and the balance between apoptotic and anti-apoptotic phenotypes remain only partially understood.…”
Section: Circulating Microparticles As Regulators Of Endothelial Dysfsupporting
confidence: 69%
“…Isolation, culture and treatment of human pulmonary endothelial cells, PA-SMCs and peripheral blood mononuclear cells Human pulmonary endothelial cells (P-ECs) and PA-SMCs were isolated from distal pulmonary arteries and cultured as previously described [12][13][14]. Cells (early passages ⩽5) were placed in serum-free medium for 24 h and exposed with dimethyloxaloylglycine (DMOG, 0.25 mM) (Enzo Life Sciences, Villeurbanne, France), dichloroacetate (DCA, 5 mM) (Sigma-Aldrich, Lyon, France), and recombinant Ob (10 and 100 ng·mL ) and ten times more (100 ng·mL −1 ) were used, based on the literature [15][16][17].…”
Section: Subjectsmentioning
confidence: 99%
“…Cells (early passages ⩽5) were placed in serum-free medium for 24 h and exposed with dimethyloxaloylglycine (DMOG, 0.25 mM) (Enzo Life Sciences, Villeurbanne, France), dichloroacetate (DCA, 5 mM) (Sigma-Aldrich, Lyon, France), and recombinant Ob (10 and 100 ng·mL ) and ten times more (100 ng·mL −1 ) were used, based on the literature [15][16][17]. Proliferation was assessed by 5-bromo-2-deoxyuridine (BrdU) incorporation [12].…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations